Do people drive safer when accidents are more expensive: Testing for moral hazard in experience rating schemes. (January 2015) - Vukina, Tomislav; Nestić, Danijel
Highlights: We test if people drive safer after their insurance went up due to an accident. After controlling for driving ability, we confirm the presence of moral hazard effect. We showed that, indeed, people drive safer when the accidents become more expensive. Abstract: Using individual policies and claims data from the Croatian mandatory motor insurance we test the theoretical proposition that under moral hazard, experience rated pricing scheme should generate the negative state dependence in claims, i.e. that drivers should drive more safely after they had an accident. The empirical challenge in these tests is to disentangle the state dependence from unobserved heterogeneity. We propose a simple approach based on the explicit reliance on the cost of future accidents function which is used to filter out the pure incentives effect, whereas the bonus-malus scale is used to control for pure heterogeneity. Our results confirm the existence of negative dependence in claims indicating the presence of significant moral hazard effect. Increasing a 3-year cost of having an accident by approximately US$20 decreases the probability of having an accident by 6.5%.